DEVELOPING A MARKETING MODEL TO ELEVATE PRODUCT VALUE SNAKEHEAD FISH MAE LA SING BURI PROVINCE - Siriphornwut, Natchunan; Somboonpol, Udom (Journal of Social Science and Cultural, 2023)
The purpose of this research was to study 1) characteristics and behaviors of consumers of Mae La snakehead fish products in Singburi province. 2) Marketing problems of Mae La snakehead fish products in Singburi Province. 3) Marketing patterns for Mae La snakehead fish products in Singburi Province, and 4) a marketing model development approach to elevate product value of Mae La snakehead fish products in Singburi Province. Used qualitative research with 43 key informants. The tool is in-depth interviews. It is a semi-structured interview and group chat. The data was analyzed by reduction. Singburi Province, They are general people, housewives and tourists. There are either intending to buy or driving through to stop by to buy. be a regular customer and subsequent consumers from the list various public relations media, most of the tourists come to pay homage to sacred things Traveling by car is comfortable. Both buses and private cars. The journey is relatively safe as the distance is not far from Bangkok. It is worth the trip. Due to traveling pay homage to sacred things and buy souvenirs with a variety of products. The product is unique and have a local identity. The Problems in marketing Mae La snakehead fish products Sing Buri Province are the product cannot be stored for a long time, Insufficient production capacity, high transportation prices, no promotions and communication and access to consumers is unclear. Marketing model for Mae La snakehead fish products Singburi Province is a 4P model and a marketing model development approach to raise the value of Mae La snakehead fish products. Sing Buri Province This can be done by adopting Marketing 4.0, which is a 5A marketing strategy consisting of 5 aspects: Awareness, Appeal, Ask, Action, and Advocate.